A Working Model of Slump and Recovery from Disturbances to Capital-Goods Demand in a Closed Non-Monetary Economy. (IMF Working Papers; Working Paper, 1988)
Certain long swings in activity may involve one or more non-monetary mechanisms not yet studied. Unlike the fundamentally classical 'real' theory of the business cycle refined in this decade, the emerging line of 'real' models called structuralist, such as the model here, hinges on the long time required for complete adjustment of implicit labor contracts to real shocks disturbing labor demand. The structuralist model here describes the depression and recovery resulting from shocks in time preference, the public debt, or labor supply whose impact drives up the real rate of interest and drives down the real demand-price of investment goods.